Autophagy is a gatekeeper of hepatic differentiation and carcinogenesis by controlling the degradation of Yap. Issue 1 (December 2018) - Lee, Youngmin; Noon, Luke; Akat, Kemal; Ybanez, Maria; Lee, Ting-Fang; Berres, Marie-Luise; Fujiwara, Naoto; Goossens, Nicolas; Chou, Hsin-I; Parvin-Nejad, Fatemeh; Khambu, Bilon; Kramer, Elisabeth; et al.
Abstract Activation of the Hippo pathway effector Yap underlies many liver cancers, however no germline or somatic mutations have been identified. Autophagy maintains essential metabolic functions of the liver, and autophagy-deficient murine models develop benign adenomas and hepatomegaly, which have been attributed to activation of the p62/Sqstm1-Nrf2 axis. Here, we show that Yap is an autophagy substrate and mediator of tissue remodeling and hepatocarcinogenesis independent of the p62/Sqstm1-Nrf2 axis. Hepatocyte-specific deletion of Atg7 promotes liver size, fibrosis, progenitor cell expansion, and hepatocarcinogenesis, which is rescued by concurrent deletion of Yap. Our results shed new light on mechanisms of Yap degradation and the sequence of events that follow disruption of autophagy, which is impaired in chronic liver disease. Increased levels of the Yap oncoprotein stimulate liver growth and promote hepatocarcinogenesis. Here the authors show that hepatocyte-specific loss ofAtg7 in mice leads to decreased autophagic degradation of Yap and liver overgrowth, and further establish this association in human liver cancer tissues.